Does environmental regulation improve public health? Evidence from China's Two Control Zones policy - Ningze Yang; Ziwei Liu; Yuxi Lin; Yongliang Yang; Yongliang Yang; Yongliang Yang (Frontiers Media S.A., 2023)
Improving public health is the premise of sustainable human development and an essential condition of economic growth. However, increasing severe environmental pollution poses a threat to public health. Implementing environmental regulation policy has become a meaningful way to control environmental pollution and the basis and guarantee for achieving public health. This paper aims to study the impact of environmental regulation on public health. The Two Control Zones (TCZ) policy is the earliest and stricter environmental regulation in China. Based on the policy experiment of TCZ, this paper analyzes the role of TCZ policy in improving public health using the DID model and data from 112 cities. The study finds that the TCZ policy can significantly improve public health, and this improvement effect was continuous and lagging. The results of benchmark regression show that the implementation of the TCZ policy has reduced the incidence rate of respiratory diseases in TCZ areas by 5.7%. When considering city heterogeneity in terms of economic and geographical conditions, the study further found that the impact of improvement is largest for cities in more heavily non-provincial capital and central and western regions, respectively. In addition, the results of mediating test show that TCZ policy improves public health by reducing environmental pollution. Our research fills the gap in the literature on the micro effects of environmental regulation policy on public health in developing countries. The government should prioritize environmental pollution control through reasonable environmental regulation policies. The government should strengthen environmental information disclosure to remind the public to deal with air pollution. The government and enterprises also should take various environmental protection measures to reduce air pollution emissions.